Who's Afraid of Policy Experiments? - Robert Dur; Arjan Non; Paul Prottung; Benedetta Ricci (CESifo GmbH, 2024)
In many public policy areas, randomized policy experiments can greatly contribute to our knowledge of the effects of policies and can thus help to improve public policy. However, policy experiments are not very common. This paper studies whether a lack of appreciation for policy experiments among voters may be the reason for this. Collecting survey data representative of the Dutch electorate, we find clear evidence contradicting this view. Voters strongly support policy experimentation and particularly so when they do not hold a strong opinion about the policy. In a subsequent survey experiment among a selected group of Dutch politicians, we find that politicians conform their expressed opinion about policy experiments to what we tell them the actual opinion of voters is.
Keywords: C93; D72; D78; 330; policy experiments; randomized controlled trials; voters; politicians; public policy; survey experiment; conformism